The use of Aglepristone in the treatment of pregnancy related diabetic ketoacidosis: description of a case in a bitch - Callegari, Daniela; Bresciani, Carla; Bianchi, Ezio; De Cesaris, Valeria; Parmigiani, Enrico; Bigaran, Virginia; Bigliardi, Enrico (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Gestational diabetes mellitus (GDM) is a rare disease in dogs that depends from an endogenous insulin supply that is insufficient to meet the tissues demands for the action of diabetogenic molecules like progesterone (P4), estradiol, growth hormone (GH), placental lactogen and placental cytokines. This report describes for the first time a case of GDM complicated by ketoacidosis treated with the P4 receptor blocker aglepristone. In our case aglepristone seemed to increase insulin sensitivity, helping in the resolution of ketoacidosis and of diabetes mellitus. Aglepristone may represent an effective and well tolerated therapeutic option in case of GDM.